Preprečevanje dejavnikov tveganja pred operativnim posegom in po njem - Buček Hajdarević, Irena (Obzornik zdravstvene nege, 2000)
The work of an anaesthesia nurse comprises the proceedings of nursing care in preoperative, interoperative and postoperative period. The introduction of nursing care process in anaesthesia enables holistic treatment of patients, quality of care and surveillance. It includes the standardization of nursing measures and medical technical procedures and psychological preparation of a patient for operation. Each anaesthesia and operation are strressful, intensified by fear, and the pathophysiological consequences for the entire organism are negative. An important element of psychological preparation of patient is the preoperative visit of anaesthesia nurse which enables positive communication and the statement patients needs and expectations. Studies have shown that the diminishment of fear, performed in this way is more successful than prescribing of anxiolytics. Preoperative preparation and even more so emotional support diminish patients distress, fastens recovery and diminishes the need for analgetics as well as postoperative complications and shortens hospitalization. Preoperative visit of an anasthesia nurse humanizes the exsisting anaesthesia practiceč moreover, anaesthesia nurse in this way emerges from the anonimity of the operating theatre.
Keywords: anestezija; Anesthesia; Anxiety; Cost-benefit analysis; Intraoperative complications; komunikacija; medicinske sestre; Nurse-patient relations; Nursing care; Postoperative complications; Preoperative care; Prevention and control; Quality of health care; Risk factors; stres; Stress, psychological; zdravstvena nega